Assessing the Impact of M&As’ Motives Influencing the M&A Decision Making Process in the UAE Banking Sector - Lootah, Ahmad Majid Ahmad Nasser; Al Tamimi, Hussein A. Hassan; Zervopoulos, Panagiotis D. (International Journal of Economics and Financial Issues, 2024)
A number of review studies have been conducted to provide valuable insights into the M&A decision-making process in the banking sector and factors that could have a positive and effective impact on it. This study systematically reviews and analyses the decision-making process for M&A and its related factors in 15 interviews with experts related to 10 M&A transaction in UAE banking sector from 2005 to 2021. The main findings contain that the most frequent factors affecting M&A decision-making are Regulation, Globalization, Technology and Economics. In addition, most of the M&A decision-making relevance is also affected by the internal factors of Synergy, Agency & Management Motives, Hubris Motives. The findings of this review study provide an overview of current studies and analyses of the M&A decision-making process in the banking sector and the factors that affect it.